Dictyuchus plureovulate sp. nov. - a new name of the genus Dictypleiosporus Gandhe - P.C. PALIWAL, S.C. SATI* and (Indian Phytopathology, 2009)
Dictyuchus plureovulate sp. nov. is described as revision of nom. invalid. of the genus Dictypleiosporus Gandhe nom. nov. This new species is described as plureovulate oogonia bearing isolate of Dictyuchus. The present species is compared with its nearest species Dictyuchus sterile and D. monosporus. Moreover, erecting a new genus merely on the basis of many eggs in oogonia and absence of antheridia is discarded as in Saprolegniales, the criteria for genetic identification are the formation of zoosporangia and zoospore release.